Knowledge lab on climate-resilient food systems: An analytical support facility to achieve the SDGs - International Food Policy Research Institute (International Food Policy Research Institute, 2018)
Enhancing resilience throughout our food systems is essential to addressing the impacts of climate change on food supplies, food safety, and nutrition as well as the broader development impacts of food system disruptions.